2020
DOI: 10.1159/000505437
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of Neural Component of Tumor Microenvironment in Prostate Cancer

Abstract: The tumor microenvironment (TME) plays an essential role in the development and progression of neoplasms. TME consists of the extracellular matrix and numerous specialized cells interacting with cancer cells by paracrine and autocrine mechanisms. Tumor axonogenesis and neoneurogenesis constitute a developing area of investigation. Prostate cancer (PC) is one of the most common malignancies in men worldwide. During the past years, more and more studies have shown that mechanisms leading to the development of PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 96 publications
(170 reference statements)
0
24
0
Order By: Relevance
“…Thus, we can speculate that MOR activation as the result of endogenous or exogenous opioids can trigger the release of soluble factors (i.e., nerve growth factor) that promote neurogenesis within the pancreatic cancer microenvironment (22). In our study, it is unlikely that a short period of exposure to sufentanil would trigger neurogenesis; therefore, we can speculate that elevated concentrations of locally released endorphins in patients with pain could be responsible of a high rate of neuritogenesis and perineural invasion (23). Alternatively, synthetic opioid such as fentanyl could promote neurotigenesis by regulating BNIP3 via miR-145-5 (24).…”
Section: A Possible Mechanism Of Opioid-induced Cancer Progression Is Via Activation Mor and Include Angiogenesis Tumor-induced Inflammatmentioning
confidence: 66%
“…Thus, we can speculate that MOR activation as the result of endogenous or exogenous opioids can trigger the release of soluble factors (i.e., nerve growth factor) that promote neurogenesis within the pancreatic cancer microenvironment (22). In our study, it is unlikely that a short period of exposure to sufentanil would trigger neurogenesis; therefore, we can speculate that elevated concentrations of locally released endorphins in patients with pain could be responsible of a high rate of neuritogenesis and perineural invasion (23). Alternatively, synthetic opioid such as fentanyl could promote neurotigenesis by regulating BNIP3 via miR-145-5 (24).…”
Section: A Possible Mechanism Of Opioid-induced Cancer Progression Is Via Activation Mor and Include Angiogenesis Tumor-induced Inflammatmentioning
confidence: 66%
“…who showed that the co-culture of PCa cell line with dorsal root ganglion stimulated the outgrowth of neurites and the migration of tumor cells toward the neural structures ( 6 ). PCa represents a tumor with a specific microenvironment, where reciprocal interactions between nerves and other cellular and extracellular components were observed molecularly and clinically in vitro and in vivo ( 5 , 7 , 36 , 37 ). Neurotransmitters released within the tumor microenvironment modulate the expression of genes by targeting tumor receptors affecting the biological potential of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The neural stromal compartment is responsible for a specific microenvironment which is different in benign and malignant prostatic glands ( 5 ). The glandular part of the normal prostate is supplied by cholinergic fibers while the stromal part – by adrenergic ones and peptidergic nerve fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the relationship between cancer and the tumour microenvironment has become a new issue in prostate pathobiology [32]. PARP affects reciprocal interactions between cells in the tumour microenvironment, affecting prostate tumorigenesis and its aggressiveness [17,28,[33][34][35][36].…”
Section: Relationship Between Parp and The Tumour Microenvironmentmentioning
confidence: 99%